PESAN DAKWAH PADA RUBRIK OPINI MAJALAH AN-NISA’ - Agus Saifuddin Amin; Putri Sita Fazira (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
Abstract:Magazines are one of the print media that can be used to convey da'wah messages and invite readers to return to the straight path and stay away from everything that can make them negligent. The discussion of the world of da'wah today cannot be separated from the community environment as an object of da'wah and using print media as part of da'wah and one example is An-Nisa' magazine. The writing of this thesis uses a content analysis method using a qualitative approach as a research procedure that obtains descriptive data in the form of written words or writings from observable people and actors. The purpose of this study was to find out about the contents of the message of da'wah contained in the opinion rubric of An-Nisa' magazine in the March 2020 edition. The results of the study indicate that the message of da'wah contains the meaning of all questions in the form of a set of symbols whose meaning comes from the Qur'an and sunnah in the form of messages of aqidah, sharia and morals that explain the relationship between humans and God and human relations with humans and have good character. according to Islamic law in order to create a peaceful life. All of this is conveyed to invite people, both individuals and groups through oral and written media, to follow Islamic teachings and be able to apply them in life, and aim to get a good life in this world and in the here after.